Of Feminism and its Versions in the Anglo-American Context - Durán Giménez-Rico, Isabel (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
In this article we briefly review the three waves of Anglo-American feminism applied to feminist criticism and theory, and some of the most established feminist trends in the English-speaking countries (mainly Great Britain and the United States).  From the pioneers Mary Wollstonecraft and Margaret Fuller, through particularly emblematic critics such as Virginia Woolf, Elaine Showalter, Betty Friedan, Toril Moi, or Sandra Gilbert and Susan Gubar, we reach “Black Feminism”, and the ethnic and intersectional feminisms of the third wave, to end this overview with a succinct allusion to Chicana feminism in the U.S., centered on the figure of Gloria Anzaldúa, as representative of a type of feminism aligned with hybridism, mestizaje  and cross-cultural encounters.
Keywords: Anglo-American Feminism; Waves of Feminism; Feminism and Ethnicity in the US.